Kepemipinan dalam Krisis: Strategi Mengelola Diri dan Tim untuk Pembentukan Organisasi yang Komunikatif dan Berkelanjutan - Anwar, Khairul (Maliki Interdisciplinary Journal, 2026)
Leadership in times of crisis is a crucial strategy that must be possessed by any leader. A leader serves as the main component in determining the future direction of an organization. A person can be considered a true leader when they are able to bring meaningful change to the organization, which can be realized by facilitating new innovations as tangible evidence of the organization’s progress. This principle must serve as guidance for every individual, especially as leadership qualities are greatly needed in today’s era of globalization. Considering the diverse dynamics within modern organizations, communication among team members is essential to maintaining harmonious relationships. A shared goal becomes easier to achieve when supported by the multitude of ideas and perspectives contributed by each individual. These collective insights must be utilized as valuable resources in achieving the common objectives established from the beginning. This study also aims to analyze strategies and new breakthroughs for shaping the character of a critical leader. Therefore, the results of this research are expected to serve as a reference in efforts to build a communicative and sustainable organization in an increasingly challenging global era, as well as a representation of students’ real contributions in achieving Indonesia’s golden generation